Polymer-based solid electrolyte, preparation method and sodium solid-state battery thereof

By using PVDF-HFP and PAI in the polymer-based solid electrolyte, adding NaTFSI and NaDFOB as additives, and using propylene carbonate as plasticizers, the problem of insufficient performance of polymer-based solid electrolytes in the prior art is solved, and electrolytes with high room temperature ionic conductivity, mechanical strength and thermal stability are achieved, significantly improving the performance of sodium solid battery.

CN119560626APending Publication Date: 2025-03-04深圳毅华新能源有限公司 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411663520.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing polymer-based solid electrolytes have shortcomings in room temperature ionic conductivity, mechanical properties, thermal stability and electrochemical windows, limiting their application in sodium solid state batteries.

Method used

Poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) is blended with polyamide-imide (PAI), and sodium bis(trifluoromethylsulfonyl)imide (NaTFSI) and sodium difluorooxalic acid borate (NaDFOB) are added as additives, and the plasticizer propylene carbonate (PC) is used as plasticizers to obtain high-performance polymer-based solid electrolytes through specific preparation methods.

Benefits of technology

The room temperature ionic conductivity, mechanical strength and thermal stability of polymer-based solid electrolytes have been significantly improved, the electrochemical window has been broadened, and the cycle stability and structural safety of sodium solid batteries have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560626A_ABST
    Figure CN119560626A_ABST
Patent Text Reader

Abstract

The invention relates to a polymer-based solid electrolyte, a preparation method and a sodium solid-state battery thereof. The polymer-based solid electrolyte comprises the following components in parts by weight: 0.8-1.2 parts of poly (vinylidene fluoride hexafluoropropylene), 0.002-0.02 part of polyamide-imide and 0.2-0.6 part of an auxiliary agent, the polymer-based solid electrolyte further comprises a plasticizer, and the volume mass ratio of the plasticizer to the poly (vinylidene fluoride hexafluoropropylene) is (0.8-1.2) ml: 1g. The polymer-based solid electrolyte disclosed by the invention has relatively high ionic conductivity, and the cycle life of a battery under high-rate and high-temperature conditions can be effectively prolonged. According to the sodium solid-state battery prepared from the polymer-based solid-state electrolyte, the problems of serious side reaction and thermal runaway of the electrolyte and an electrode interface are effectively solved, and the cycling stability and the structural safety of the sodium solid-state battery can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer-based solid electrolyte, a preparation method and a sodium solid-state battery thereof, and belongs to the field of solid-state batteries. Background Art

[0002] As the supply of traditional fossil energy becomes increasingly tight, the world's energy system is bound to transform and upgrade to clean energy. Among today's energy storage technologies, electrochemical energy storage with high efficiency, low cost and long cycle life has received much attention and has become a hot topic in the field of scientific research. After years of development, sodium-ion batteries have gradually matured and have been put into practical use in various industries. However, the commercialized sodium-ion batteries currently mainly use organic electrolytes, which brings with them safety hazards such as flammability, explosion, and electrolyte leakage.

[0003] Solid electrolytes have the advantages of excellent thermal stability, mechanical properties and high energy density, and have attracted widespread attention. They can be mainly divided into inorganic solid electrolytes, solid polymer electrolytes and organic-inorganic composite electrolytes. Although inorganic solid electrolytes have high ionic conductivity, their poor interface stability and interface contact rigidity limit their development. In contrast, solid polymer electrolytes (i.e., polymer-based solid electrolytes), as a type of complex formed by coordination between salt and polymer matrix materials, have shown unique advantages in the field of batteries. Their good flexibility, simple production process and relatively low cost provide favorable conditions for large-scale production. In addition, polymer electrolytes have excellent softness and wettability, and can achieve close contact with the interface of electrode materials, which is crucial to improving battery performance. However, polymer electrolytes also face a series of challenges. Their low room temperature ionic conductivity limits their performance in practical applications to a certain extent. At the same time, the electrochemical window of polymer electrolytes is narrow, their compatibility with negative electrode materials needs to be strengthened, and their mechanical properties need to be further improved. In addition, current polymer electrolytes have poor thermal stability and will generate a lot of heat during high-rate and long-term use of the battery, which can easily lead to thermal runaway of the battery. Therefore, for the development of long-term and high-rate sodium solid-state batteries, it is crucial to obtain an electrolyte membrane with high room-temperature ionic conductivity, high mechanical strength, and high thermal stability.

[0004] Chinese invention patent application specification CN116315074 A discloses a polymer-based sodium ion solid electrolyte, comprising the following mass percentage components: 35-50% olefin polymer, 45-60% sodium salt and 5-15% functional additive; the sodium salt is sodium bis(fluorosulfonyl)imide and / or sodium bis(trifluoromethylsulfonyl)imide; the functional additive is sodium difluorooxalate borate and / or sodium bisoxalate borate; the electrolyte also includes DMF, and the volume mass ratio of DMF to the olefin polymer is 7-12ml / g. The olefin polymer is at least one of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene) copolymer, poly(vinylidene fluoride-trifluoroethylene) copolymer, poly(vinylidene fluoride-tetrafluoroethylene) copolymer and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) copolymer. However, the room temperature ionic conductivity of the polymer solid electrolyte can only reach 4.3×10 -4 S cm -1 After being assembled into a solid-state battery, the charge and discharge cycle test was carried out at room temperature at a rate of 0.5C. The number of cycles with a capacity retention rate of not less than 80% did not exceed 750 weeks, which still has a lot of room for improvement. In addition, this technology does not solve the problem of stable cycling and thermal runaway of the battery at high rates, and the residual DMF solvent will also cause serious interface side reactions. Summary of the invention

[0005] In view of the shortcomings of the prior art, one of the objects of the present invention is to provide a polymer-based solid electrolyte with better electrochemical performance; the second object of the present invention is to provide a method for preparing a polymer-based solid electrolyte; the third object of the present invention is to provide a sodium solid-state battery.

[0006] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0007] A polymer-based solid electrolyte comprises 0.8-1.2 parts of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), 0.002-0.02 parts of polyamide-imide (PAI), and 0.2-0.6 parts of an additive; the polymer-based solid electrolyte also comprises a plasticizer, and the volume mass ratio of the plasticizer to the poly(vinylidene fluoride-hexafluoropropylene) is 0.8-1.2 ml:1 g.

[0008] Furthermore, the polymer-based solid electrolyte includes 0.9-1.1 parts of poly(vinylidene fluoride-hexafluoropropylene), 0.003-0.018 parts of polyamide-imide, and 0.3-0.5 parts of an additive; the polymer-based solid electrolyte also includes a plasticizer, and the volume mass ratio of the plasticizer to poly(vinylidene fluoride-hexafluoropropylene) is 0.9-1.1 ml: 1 g.

[0009] Furthermore, the polymer-based solid electrolyte includes 0.95-1.05 parts of poly(vinylidene fluoride-hexafluoropropylene), 0.005-0.015 parts of polyamide-imide, and 0.35-0.45 parts of an additive; the polymer-based solid electrolyte also includes a plasticizer, and the volume mass ratio of the plasticizer to poly(vinylidene fluoride-hexafluoropropylene) is 0.95-1.05ml:1g.

[0010] Furthermore, the auxiliary agent is sodium bis(trifluoromethylsulfonyl)imide (NaTFSI) and / or sodium difluorooxalatoborate (NaDFOB). Thus, the addition of NaTFSI can further improve the mechanical strength and room temperature ionic conductivity of the polymer-based solid electrolyte, and the addition of NaDFOB can be used as a film-forming additive to form a stable SEI film at the interface between the electrode and the electrolyte, which helps to further improve the battery cycle stability and broaden the electrochemical window.

[0011] Preferably, the auxiliary agent is composed of sodium bis(trifluoromethylsulfonyl)imide and sodium difluorooxalatoborate in a mass ratio of 0.2-0.4:0.08-0.2.

[0012] Furthermore, the plasticizer is propylene carbonate (PC). Thus, using organic small molecule PC as a plasticizer can further promote the dissociation of sodium salt, reduce the overall internal resistance of the polymer electrolyte, and reduce the crystallinity of the polymer, which helps to further improve the transmission rate of sodium ions in the electrolyte and the interface wettability.

[0013] Furthermore, the weight average molecular weight of poly(vinylidene fluoride-hexafluoropropylene) is 200,000-600,000, further 300,000-500,000, further 350,000-450,000, and preferably 320,000-420,000.

[0014] Furthermore, the intrinsic viscosity of the polyamide-imide (prepared as a 0.5 wt % polyamide-imide NMP solution, tested at 25° C.) is greater than 0.3, preferably greater than 0.5.

[0015] Furthermore, the polymer-based solid electrolyte is in the form of a film, and its thickness is 300-900 μm, preferably 500-700 μm.

[0016] Based on the same inventive concept, the present invention also provides: a method for preparing the polymer-based solid electrolyte as described above, comprising the following steps:

[0017] S1. Under a protective atmosphere, poly(vinylidene fluoride-hexafluoropropylene), polyamide-imide, a plasticizer and an organic solvent are uniformly mixed according to a formula to obtain a membrane solution;

[0018] The volume mass ratio of the organic solvent to poly(vinylidene fluoride-hexafluoropropylene) is 8-12 ml: 1 g;

[0019] S2. Under a protective atmosphere, the membrane solution and the additive are mixed uniformly to obtain an electrolyte slurry;

[0020] S3, coating the electrolyte slurry on a mold, and obtaining a polymer-based solid electrolyte after drying.

[0021] Furthermore, in S1, the organic solvent is acetone; preferably, the mixing is carried out at 55-65°C, whereby the use of a suitable temperature is conducive to the full and complete dissolution of the polymer and prevents the polymer from failing due to depolymerization, breakage, loss of side groups, etc. caused by excessively high temperature.

[0022] Further, in S2, the mixture is stirred and mixed at a rate of 500-1000 r / min at 45-65° C. for 10-20 h.

[0023] Furthermore, in S3, the drying method is vacuum drying. Preferably, when drying, first stand for 4-8 minutes, then vacuumize for 6-14 minutes to remove the organic solvent; more preferably, first stand for 5-7 minutes, then vacuumize for 8-12 minutes. As a result, the organic solvent can evaporate evenly in a short time, and form a semi-gel film on the surface of the membrane, reducing the influence of the airflow on the membrane morphology during subsequent vacuuming, so that the organic solvent inside the membrane can be discharged more evenly during vacuuming, and the membrane surface is prevented from generating ripples or water droplet-shaped lines, thereby obtaining a higher quality polymer-based solid electrolyte. At the same time, the method is simple and fast, and can effectively shorten the process time.

[0024] Optionally, the mold is a glass plate.

[0025] Based on the same inventive concept, the present invention also provides: a sodium solid-state battery, wherein the electrolyte of the sodium solid-state battery is the polymer-based solid-state electrolyte as described above or a polymer-based solid-state electrolyte prepared by the preparation method as described above.

[0026] In the present invention, PAI and PVDF-HFP are blended to form a porous skeleton, which can enhance the mechanical properties, flame retardancy and thermal stability of the polymer solid electrolyte while improving the electrochemical properties of the material under high current and high temperature.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The polymer-based solid electrolyte of the present invention has high ionic conductivity, which can effectively prolong the battery cycle life under high rate and high temperature conditions. Its room temperature ionic conductivity can reach 0.9 mS cm -1The assembled sodium solid-state battery has a discharge capacity of more than 90 mAh / g at a rate of 5C, can be stably cycled for 1,000 times, and has a capacity retention rate of more than 80%.

[0029] (2) The preparation method of the present invention is simple, easy to prepare on a large scale, and has good prospects for industrial application.

[0030] (3) The sodium solid-state battery prepared by the polymer-based solid-state electrolyte of the present invention effectively solves the problems of severe side reactions at the electrolyte and electrode interface and thermal runaway, greatly improves the cycle stability and structural safety of the sodium solid-state battery, and has good application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a graph showing the room temperature ionic conductivity test results of Example 1 (PTD) of the present invention and Comparative Example 1 (TD).

[0032] Figure 2 It is a graph of the electrochemical window (under 10 μA conditions) test results of Example 1 (PTD) of the present invention and Comparative Example 1 (TD).

[0033] Figure 3 It is a graph showing the rate performance test results of Example 1 (PTD) of the present invention and Comparative Example 1 (TD).

[0034] Figure 4 It is a graph showing the electrochemical performance test results of Example 1 (PTD) of the present invention and Comparative Example 1 (TD) at 60°C.

[0035] Figure 5 It is a graph showing the electrochemical performance test results of Example 1 (PTD) of the present invention and Comparative Example 1 (TD) at a 5C rate.

[0036] Figure 6 It is a flame retardant performance test result diagram of the polymer-based solid electrolyte of Example 1 (PTD) of the present invention and Comparative Example 1 (TD).

[0037] Figure 7 These are digital photos of the polymer-based solid electrolyte (a) before drying and the polymer-based solid electrolyte (b) after direct vacuum drying for 15 minutes in Comparative Example 2 of the present invention.

[0038] Figure 8 These are digital photos of the polymer-based solid electrolyte (a) before drying in Comparative Example 3 of the present invention and the polymer-based solid electrolyte (b) after being allowed to stand for 3 minutes and then vacuum dried for 12 minutes.

[0039] Fig. 9These are digital photos of the polymer-based solid electrolyte (a) before drying and the polymer-based solid electrolyte (b) after being allowed to stand for 5 minutes and then vacuum dried for 10 minutes in Example 1 of the present invention.

[0040] Fig.10 This is a diagram showing the test results of stretching the polymer-based solid electrolyte of Example 1 of the present invention, wherein: Fig.10 a. Fig.10 b. Fig.10 The pulling force of c increases successively. DETAILED DESCRIPTION

[0041] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0042] Example 1

[0043] This embodiment provides a polymer-based solid electrolyte and a sodium solid-state battery thereof, and the preparation steps are as follows:

[0044] Step 1. Weigh the raw materials according to the following formula: poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight 400000) 1g; polyamide-imide (PAI, manufacturer Solvay, model 4000TF) 0.01g; sodium bis(trifluoromethylsulfonyl)imide (NaTFSI) 0.28g; sodium difluorooxalatoborate (NaDFOB) 0.12g; propylene carbonate (PC) 1ml; acetone (AC) 10ml. In an atmosphere-protected environment, poly(vinylidene fluoride-hexafluoropropylene), polyamide-imide, propylene carbonate, and acetone are first placed in a serum bottle, and stirred at a temperature of 60°C and a rotation speed of 800 r / min for 24 hours to obtain a uniform light yellow membrane solution; sodium bis(trifluoromethylsulfonyl)imide and sodium difluorooxalatoborate are then added to the above membrane solution, and stirred at 50°C and a rotation speed of 600 r / min for 12 hours to obtain an electrolyte slurry; then, the obtained electrolyte slurry is scraped on a glass plate with a 1000 μm scraper (the coating thickness is controlled to be 1000 μm), and then dried in a vacuum oven at room temperature for 5 minutes, and then vacuumed for 10 minutes to remove the organic solvent to obtain a polymer-based solid electrolyte (self-supporting quasi-solid polymer electrolyte, film-like).

[0045] Step 2: Based on the obtained polymer-based solid electrolyte, a stainless steel / polymer-based solid electrolyte / stainless steel battery is assembled, and an electrochemical workstation is used to perform an AC impedance spectroscopy test and a linear sweep voltammetry test; the room temperature ionic conductivity and electrochemical window data of the polymer electrolyte are calculated and the results are shown in Table 1.

[0046] Step 3: Based on the obtained polymer-based solid electrolyte, assemble the NVP@C||Na full battery, and perform room temperature and high temperature cycle performance tests. The specific operation is: within the electrochemical window range of 2.0-3.8V, use 5C and 1C rates to perform charge and discharge cycle tests at room temperature and high temperature 60°C, respectively, test the cycle performance of the above battery, and count the number of cycles with a capacity retention rate of 80%. The data results of this example are recorded in Table 1.

[0047] Among them, the positive electrode sheet is made by mixing the positive electrode material (NVP), conductive agent (SP) and binder (PVDF) in a mass ratio of 8:1:1, coating them on the carbon-coated aluminum current collector, placing them in a vacuum oven at 80°C for vacuum drying for 12 hours, taking them out, and cutting them with a cutter with a diameter of 12 mm to obtain the positive electrode sheet.

[0048] Battery assembly: The positive electrode shell, positive electrode sheet, polymer-based solid electrolyte, sodium sheet (negative electrode), steel sheet, and negative electrode shell are packaged in this order to obtain the NVP@C|Na full battery.

[0049] After testing, the NVP@C|Na full battery of the present invention has a discharge specific capacity of 92.14 mAh / g at a rate of 5C, a stable cycle of 1000 cycles, and a capacity retention rate of up to 82.5%, showing excellent electrochemical performance.

[0050] In addition, a Na||Na symmetric battery was assembled in the order of negative electrode shell, sodium sheet, polymer-based solid electrolyte, sodium sheet, and positive electrode shell. The assembled Na||Na symmetric battery was 0.1 mA / cm 2 The deposition and stripping can be stably carried out for 2000h at a current density of .

[0051] Comparative Example 1

[0052] Compared with Example 1, PAI was not added in Comparative Example 1; the remaining conditions and test types were the same as those in Example 1.

[0053] Example 2

[0054] Compared with Example 1, the amount of PAI added in Example 2 is 0.005 g; the other conditions and test types are the same as those in Example 1.

[0055] Example 3

[0056] Compared with Example 1, the amount of PAI added in Example 3 is 0.015 g; the other conditions and test types are the same as those in Example 1.

[0057] Example 4

[0058] Compared with Example 1, the amount of PAI added in Example 4 is 0.02 g; the other conditions and test types are the same as those in Example 1.

[0059] Table 1. Table of relevant performance test results of various embodiments and comparative examples

[0060]

[0061] It can be seen that the addition of PAI can significantly improve the room temperature ionic conductivity of polymer-based solid electrolytes (see Figure 1 ), the possible reason is that the addition of PAI can reduce the crystallinity of PVDF-HFP. In addition, the amide groups in PAI form complexes with sodium ions, promoting the dissociation of sodium salts, thereby improving the room temperature ionic conductivity of the polymer electrolyte. In addition, it can be seen that the higher the amount of PAI added, the higher the room temperature ionic conductivity of the polymer electrolyte. When the amount of PAI added reaches a certain level, the room temperature ionic conductivity of the polymer electrolyte decreases, and the cycle performance of the corresponding battery also decreases. At the same time, the addition of PAI can significantly broaden the electrochemical window of polymer-based solid electrolytes, see Figure 2 .

[0062] See also Figure 3 Since the ion transport capacity of the polymer-based solid electrolyte of the present invention is enhanced, its rate performance is also significantly improved. At a rate of 8C, the discharge specific capacity is as high as 73 mAh / g, which is greatly improved compared with Comparative Example 1 (10 mAh / g); in addition, the discharge specific capacity of the polymer-based solid electrolyte of the present invention is also increased by 10 mAh / g.

[0063] See also Figure 4 The battery corresponding to the polymer-based solid electrolyte of the present invention was stably cycled at 60°C at a rate of 1C for 500 cycles, and the capacity retention rate was 76%; while in the case where PAI was not added, the battery failed after about 270 cycles and could not continue to cycle stably. It can be inferred that the polymer-based solid electrolyte of the present invention has better thermal stability.

[0064] See also Figure 5 The battery corresponding to the polymer-based solid electrolyte of the present invention can stably cycle 1000 times under high rate (5C) conditions, and its discharge specific capacity is 85 mAh / g, and the capacity retention rate is as high as 89.4%, which is much better than Comparative Example 1.

[0065] See also Figure 6 The polymer-based solid electrolytes of Example 1 and Comparative Example 1 were flame-retardantly tested using the same igniter and the same firepower. The results showed that the polymer-based solid electrolyte of Comparative Example 1 was easily ignited and continued to burn, while the polymer-based solid electrolyte of Example 1 was not easily ignited. This shows that the polymer-based solid electrolyte of the present invention is safer.

[0066] Comparative Example 2

[0067] Compared with Example 1, in step 1 of Comparative Example 2, the organic solvent was directly removed by vacuuming in a vacuum oven for 15 minutes (without standing treatment); the other conditions and test types were the same as those in Example 1.

[0068] Comparative Example 3

[0069] Compared with Example 1, in step 1 of Comparative Example 3, the organic solvent was removed by standing in a vacuum oven for 3 minutes and evacuating for 12 minutes (without standing treatment); the other conditions and test types were the same as those in Example 1.

[0070] from Figures 1 to 3 It can be seen that there are many water droplet-shaped ripples on the surface of the polymer-based solid electrolyte membrane that has not been left to stand. The possible reason is that the wind force is too strong during vacuuming, resulting in uneven evaporation of the solvent; after standing for 3 minutes and then vacuuming, the flatness of the surface of the polymer-based solid electrolyte membrane has been significantly improved, but there are still small water droplet lines; after standing for 5 minutes and then vacuuming, the surface of the polymer-based solid electrolyte membrane has good flatness and no water droplet lines. The possible reason is that the organic solvent has achieved uniform evaporation in a short time and formed a semi-gel film on the membrane surface, which can reduce the influence of airflow on the membrane morphology during subsequent vacuuming, so that the organic solvent inside the membrane can be discharged more evenly during vacuuming, and the ripples or water droplet-shaped lines on the membrane surface can be avoided, thereby obtaining a higher quality polymer-based solid electrolyte. At the same time, this method is simple and fast, and can effectively shorten the process time.

[0071] from Figure 4 It can be seen that the polymer-based solid electrolyte membrane prepared by the present invention has high tensile strength and flexibility. Under the pulling of large stress, the electrolyte membrane still maintains good elasticity and does not break.

[0072] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

Claims

1. A polymer-based solid electrolyte, characterized in that: It includes 0.8-1.2 parts of poly(vinylidene fluoride-hexafluoropropylene), 0.002-0.02 parts of polyamide-imide, and 0.2-0.6 parts of additives; the polymer-based solid electrolyte also includes a plasticizer, and the volume mass ratio of the plasticizer to poly(vinylidene fluoride-hexafluoropropylene) is 0.8-1.2ml:1g.

2. The polymer-based solid electrolyte according to claim 1, characterized in that: The polymer-based solid electrolyte includes poly(vinylidene fluoride-hexafluoropropylene) 0.9-1.1 parts, polyamide-imide 0.003-0.018 parts, auxiliary agent 0.3-0.5 parts; the polymer-based solid electrolyte also includes a plasticizer, and the volume mass ratio of the plasticizer to poly (vinylidene fluoride-hexafluoropropylene) is 0.9-1.1 ml: 1g.

3. The polymer-based solid electrolyte according to claim 1, characterized in that: The polymer-based solid electrolyte includes 0.95-1.05 parts of poly(vinylidene fluoride-hexafluoropropylene), 0.005-0.015 parts of polyamide-imide, and 0.35-0.45 parts of an additive; the polymer-based solid electrolyte also includes a plasticizer, and the volume mass ratio of the plasticizer to poly(vinylidene fluoride-hexafluoropropylene) is 0.95-1.05ml:1g.

4. The polymer-based solid electrolyte according to any one of claims 1 to 3, characterized in that: The auxiliary agent is sodium bis(trifluoromethylsulfonyl)imide and / or sodium difluorooxalate borate; preferably, the auxiliary agent is composed of sodium bis(trifluoromethylsulfonyl)imide and sodium difluorooxalate borate in a mass ratio of 0.2-0.4:0.08-0.

2.

5. The polymer-based solid electrolyte according to any one of claims 1 to 3, characterized in that: The plasticizer is propylene carbonate.

6. The method for preparing a polymer-based solid electrolyte according to any one of claims 1 to 5, characterized in that: The steps include: S1. Under a protective atmosphere, poly(vinylidene fluoride-hexafluoropropylene), polyamide-imide, a plasticizer and an organic solvent are uniformly mixed according to a formula to obtain a membrane solution; The volume mass ratio of the organic solvent to poly(vinylidene fluoride-hexafluoropropylene) is 8-12 ml: 1 g; S2. Under a protective atmosphere, the membrane solution and the additive are mixed uniformly to obtain an electrolyte slurry; S3, coating the electrolyte slurry on a mold, and obtaining a polymer-based solid electrolyte after drying.

7. The preparation method according to claim 6, characterized in that: In S1, the organic solvent is acetone.

8. The preparation method according to claim 6, characterized in that: In S2, the mixture is stirred at 45-65°C and a rate of 500-1000 r / min for 10-20 h.

9. The preparation method according to claim 6, characterized in that: In S3, the drying method is vacuum drying; preferably, during drying, the system is first allowed to stand for 4-8 minutes, and then vacuumized for 6-14 minutes; more preferably, the system is first allowed to stand for 5-7 minutes, and then vacuumized for 8-12 minutes.

10. A sodium solid-state battery, characterized in that: The electrolyte of the sodium solid-state battery is a polymer-based solid electrolyte as described in any one of claims 1 to 5 or a polymer-based solid electrolyte prepared by the preparation method as described in any one of claims 6 to 8.

Citation Information

Patent Citations

  • Polymer sodium ion solid electrolyte as well as preparation method and application thereof

    CN116315074A